Elaboración del manual de funciones para la Compañía Housing Ingenieros SAS (2020)
Housing Ingenieros SAS, is a simplified stock company registered in October 2011 with registered address in the city of Cota. This company is mainly engaged in the completion and finishing of buildings and civil engineering works, Wireless Telecommunications activities, specialized design activities, and construction of other Civil Engineering works. The company has professional and specialized personnel for each of the services it provides. Its organizational structure is made up of the administrative department, project department, quality department, customer service department. Currently Housing Ingenieros SAS, provides its services nationwide providing solutions, in the completion of buildings and other construction projects, the maintenance and operation of wireless telecommunications networks, and in specialized activities in civil works. The company currently does not have the functions manual, and this has generated uncertainty in its collaborators about what they must fully comply with so that each of their projects is delivered with the highest standards of quality and prestige.